Seaward migrating Atlantic salmon smolts with low levels of gill Na+, K+ -ATPase activity : is sea entry delayed? - Strand, Jo Espen Tau; Davidsen, Jan Grimsrud; Jørgensen, Even Hjalmar; Rikardsen, Audun H. (Environmental Biology of Fishes, 2010)
Two groups of migrating wild Atlantic salmon (Salmo salar) smolts caught within a 1 week interval in the River Alta, northern Norway, were tagged with acoustic transmitters and measured for gill Na+, K+ -ATPase activity in order to compare their smolt status with timing of sea entry. The first group of smolts had low levels of gill Na+, K+ -ATPase activity and resided in the lower part of the river twice as long as the second group that had high levels of gill Na+, K+ -ATPase activity. This indicates that early migrating smolts may not be completely physiologically adapted for salt water and delay their sea entry, thereby also synchronizing their seaward migration with the later migrating smolts.Seaward migrating Atlantic salmon smolts with low levels of gill Na+, K+ -ATPase activity; is sea entry delayed? [Published online: 16 november 2010]